Sistem Navigasi Robot Quadruped 12 DoF dengan Algoritma Dynamic Programing - Achmad Firman Choiri (Jurnal Teknologi Informasi dan Terapan, 2023)
The quadruped robot that has 4 legs as a means of locomotion can move from the previous place because it has a degree of freedom (DOF) on each leg. Of the 3 DOFs, each leg requires an algorithm to be able to create a precise navigation system. This is done because quadruped robots are more difficult to find balance in maneuvering. After all, this robot only has 3 fulcrum points in each movement on one leg of the robot. Giving the right algorithm to each leg of the robot will create a fit of movement where 3 legs will always be the pedestal when 1 leg of the robot is being lifted to ensure the robot does not collapse. Supported by the right algorithm, it will produce a good navigation system for the robot. In this study, the servo used was the Hitec HS-645MG servo type. To support testing on the navigation system in this study is to use ultrasonic sensors as distance reading input sensors in supporting robots in the navigation process. So that the robot can be controlled according to the input of the ultrasonic sensor that is inputted so that the robot does not touch the obstacles around it. (Abstract)